Blood oxidative stress markers after ultramarathon swimming - Kabasakalis, A.; Kyparos, A.; Tsalis, G.; Loupos, D.; Pavlidou, A.; Kouretas, D. (The Journal of Strength and Conditioning Research, 2011)
Data on redox balance in response to marathon swimming are lacking, whereas findings from studies using other types of ultraendurance exercise are controversial. The aim of the present study was to investigate the effect of ultramarathon swimming on selective blood oxidative stress markers. Five well-trained male swimmers aged 28.8 (6.0) years participated in the study. Blood samples were obtained before and after the ultramarathon swimming, for full blood count analysis and determination of protein carbonyls, thiobarbituric acid-reactive substances (TBARS), and total antioxidant capacity (TAC). The swimmers swam 19.4 (3.4) hours, covering 50.5 (15.0) km. Hematocrit and erythrocyte count, and leukocyte, neutrophil and monocyte counts were significantly elevated after swimming, whereas protein carbonyls, TBARS and TAC did not significantly change. The findings of the present study indicate that well-trained swimmers were able to regulate a redox homeostasis during ultra-long duration swimming. It is also postulated that the relatively low intensity of marathon swimming may not be a sufficient stimulus to induce oxidative stress in well-trained swimmers. The fact that low-intensity long-duration exercise protocols are not associated with oxidative damage is useful knowledge for coaches and athletes in scheduling the content of the training sessions that preceded and followed these exercise protocols.